COVID-19: minimising contaminated aerosol spreading during CPAP treatment. Issue 6 (15th July 2020) - Donaldsson, Snorri; Naver, Lars; Jonsson, Baldvin; Drevhammar, Thomas
Abstract : Background: The COVID-19 pandemic has raised concern for healthcare workers getting infected via aerosol from non-invasive respiratory support of infants. Attaching filters that remove viral particles in air from the expiratory limb of continuous positive airway pressure (CPAP) devices should theoretically decrease the risk. However, adding filters to the expiratory limb could add to expiratory resistance and thereby increase the imposed work of breathing (WOB). Objective: To evaluate the effects on imposed WOB when attaching filters to the expiratory limb of CPAP devices. Methods: Two filters were tested on three CPAP systems at two levels of CPAP in a mechanical lung model. Main outcome was imposed WOB. Results: There was a minor increase in imposed WOB when attaching the filters. The differences between the two filters were small. Conclusion: To minimise contaminated aerosol generation during CPAP treatment, filters can be attached to expiratory tubing with only a minimal increase in imposed WOB in a non-humidified environment. Care has to be taken to avoid filter obstruction and replace filters as recommended.